Pengaruh Pembiayaan Murabahah, Mudharabah, Dan Musyarakah Terhadap Profitabilitas Bank Umum Syariah - Firdayati, Elda; Canggih, Clarashinta (Jurnal Ekonomika dan Bisnis Islam, 2020)
In increasing the assets of Islamic banks, they certainly need funding. Return on Assets (ROA) is a ratio that has the function of increasing banking assets. This study aims to determine the effect of murabaha, mudaraba and musharaka financing on profitability projected on ROA using objects, namely 9 Islamic banks in Otoritas Jasa Keuangan (OJK) which have reached the research criteria. Data from this study are in the form of financial statements from the bank’s website for the 2014-2018 period. The partial results of the study are murabahah, mudharabah, and musyarakah financing have no influence on ROA, while simultaneous murabahah, mudharabah and musyarakah financing do not have an influence on ROA.